Section 7.5 Generating Functions for Bernoulli-based Distributions
Moment Generating Functions 5.5.1 can be derived for each of the distributions in this chapter.Theorem 7.5.1. Moment Generating Function for Bernoulli.
Proof.
Theorem 7.5.2. Moment Generating Function for Geometric.
Proof.
Presuming \(e^t (1-p) \lt 1\text{,}\)
where we used the geometric series to convert the sum. The second form comes by dividing through by \(e^t\text{.}\)
Corollary 7.5.3. Geometric Properties via Moment Generating Function.
For the Geometric variable X,
Proof.
Using the second form for M(t),
and therefore
Continuing with the second derivative,
and therefore
which is the squared mean plus the variance for the geometric distribution.
Theorem 7.5.4. Moment Generating Function for Binomial.
Proof.
where we used the binomial theorem to simplify the sum.
Corollary 7.5.5. Binomial Properties via Moment Generating Function.
Proof.
Taking the derivative with respect to t,
and evaluating at t=0 gives
Again, taking another derivative with respect to t,
and evaluating at t=0 gives
Theorem 7.5.6. Moment Generating Function for Negative Binomial.
Proof.
Using the a previous theorem 7.4.5 justifying the Negative Binomial probability function with \(a = p e^t\) and \(b = 1-p\) and by changing variables to \(u = x-r\) gives
noting that the last summation is the the sum of a negative binomial probability function over its entire range.
It should be noted one may also rewrite the summation and appeal directly to the Negative Binomial Series 7.4.1 to also prove this result.
Corollary 7.5.7. Negative Binomial Properties via Moment Generating Function.
Proof.
Taking the derivative with respect to t,
and evaluating at t=0 gives
OOPS...don't need the (1-p) on top. Again, taking another derivative with respect to t,
and evaluating at t=0 gives
xxxxxxxxxx
var('t,x,n,p,mu,r')
assume(p < 1)
assume(p > 0)
f = binomial(x+r-1,r-1)*p^r*(1-p)^x
M = sum(e^(t*x)*f,x,0,infinity).factor()
show(M)
show(M(t=0))
Mt = derivative(M,t).factor()
show(Mt(t=0).simplify())
Mtt = derivative(Mt,t)
show(Mtt)
show(Mtt(t=0).simplify())
show((Mtt(t=0)-Mt(t=0)^2).factor())